An Application of Water Pollution Index (PI) to Describe the Water Quality of Ciwalen River, Garut Regency - Marcellina Kristin; Taufik Taufikurahman; Devi Nandita Choesin (Universitas Islam Raden Rahmat, Malang, 2025)
Garut Regency is one of the famous leather producing areas in Indonesia. The existence of leather tanning industry gives some positive impact in economic but also some negative impact to the environment. This study aims to analyze the condition of Ciwalen River using the Pollution Index (PI) method to monitor the river water quality. Water sampling was carried out using the grab sampling technique during dry and rainy season, on June and December 2024. The parameters measured include BOD, COD, TSS, pH, oil and fat, ammonia, total chrome, and sulfide concentration. These parameters were used to calculate Water Pollution Index (PI). Based on the PI, the condition of the Ciwalen river that passes through the Sukaregang leather tanning industry area is polluted. In dry season, the condition of the water cannot be used for drinking water and is moderately polluted for class II-IV needs such as livestock, fisheries, and plant watering. While in rainy season there is a decrease in polluted conditions to moderate polluted for classes I-III and light polluted for class IV due to higher debit and self purification process.